Proceedings of the 2020 Conference on Empirical Methods in Natural Language Processing (EMNLP) 2020
DOI: 10.18653/v1/2020.emnlp-main.454
|View full text |Cite
|
Sign up to set email alerts
|

Multi-view Story Characterization from Movie Plot Synopses and Reviews

Abstract: This paper considers the problem of characterizing stories by inferring properties such as theme and style using written synopses and reviews of movies. We experiment with a multi-label dataset of movie synopses and a tagset representing various attributes of stories (e.g., genre, type of events). Our proposed multi-view model encodes the synopses and reviews using hierarchical attention and shows improvement over methods that only use synopses. Finally, we demonstrate how can we take advantage of such a model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The MovieLens data set, however, is mainly suitable for CF approaches and has limited textual content, which can affect the performance of CB approaches [28]. Thus, all items in the MovieLens data set are further enriched with plot synopses which are available in the movie plot synopses with tags (MPST) data set [29]. MPST is a corpus of ≈70 fine-grained tags and their associations with ≈14 K plot synopses of movies.…”
Section: Methodsmentioning
confidence: 99%
“…The MovieLens data set, however, is mainly suitable for CF approaches and has limited textual content, which can affect the performance of CB approaches [28]. Thus, all items in the MovieLens data set are further enriched with plot synopses which are available in the movie plot synopses with tags (MPST) data set [29]. MPST is a corpus of ≈70 fine-grained tags and their associations with ≈14 K plot synopses of movies.…”
Section: Methodsmentioning
confidence: 99%
“…In the paper, they tackled the problem of simile generation. Kar et al [2020] tackled story characterization from movie plot synopses and multi-view multi-labeled reviews. This study suggested the importance of considering that the different recipients of the story have their perspectives.…”
Section: How To Evaluate Story-like Textmentioning
confidence: 99%
“…Instead, our distant-supervision methodology leverages information from the conversation level to the utterance level based on a key observa-1 http://www.life1995.org.tw/ tion that the risk of suicidal ideation can often be determined by only a few utterances. Our approach also differs from previous hierarchical and multigrained approaches (Kar et al, 2020;Angelidis and Lapata, 2018) that seek to distill fine-grained information from every smaller piece of the entire input.…”
Section: Introductionmentioning
confidence: 99%